2013
DOI: 10.1182/blood-2013-03-491464
|View full text |Cite
|
Sign up to set email alerts
|

Long-term remission of T-cell large granular lymphocyte leukemia associated with rheumatoid arthritis after rituximab therapy

Abstract: Key Points Rituximab may be a safe and effective therapy in patients with both large granular lymphocyte leukemia and rheumatoid arthritis. LGLL in some patients with rheumatoid arthritis may be a reactive manifestation of chronic autoantigen stimulation rather than a true concomitant malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 18 publications
(14 reference statements)
1
23
0
4
Order By: Relevance
“…In our opinion, this is not a reasonable option for LGL leukemia. 110,111 Splenectomy. Splenectomy may be considered in patients with symptomatic splenomegaly associated or not with cyopenias.…”
Section: Second-line Therapymentioning
confidence: 99%
“…In our opinion, this is not a reasonable option for LGL leukemia. 110,111 Splenectomy. Splenectomy may be considered in patients with symptomatic splenomegaly associated or not with cyopenias.…”
Section: Second-line Therapymentioning
confidence: 99%
“…57,58 Interestingly, despite the fact that it is a T cell-mediated disease, autoimmune neutropenia may also respond to rituximab. 59 Most patients will also respond to G-CSF, although in the setting of RA, this may cause an acute exacerbation of joint symptoms.…”
Section: Autoimmune Neutropeniamentioning
confidence: 99%
“…Despite the fact that the majority of reviews about T-cell LGLL have mentioned that cutaneous involvement is rare, there are a few descriptions of different skin presentations, including nodules, ulcers, telangiectasia, and cutaneous thrombotic and necrotizing mycroangiopathy. In 1992, Helm et al described a pyoderma gangrenous-like ulcer, which was a cutaneous manifestation of LGLL [14][15][16][17]. Although we could not ascertain skin infiltration by large granular lymphocytes in our patient, the presentation of ulcers that mimicked pyoderma gangrenous in the histology suggested that this case might have represented a second atypical cutaneous presentation.…”
Section: Discussionmentioning
confidence: 47%